Do acquaintances and friends make us learn? Social capital and lifelong learning in Germany - Anna-Elisabeth Thum; Miroslav Bablavy (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper examines the relationship between social capital and adult learning. We test this association empirically using measures of various types of social capital and adult learning based on the German Socioeconomic Panel. We use predetermined measures of social capital to exclude social skills or friends encountered during the adult education class. Fixed effects for latent underlying factors such as deep personality traits and instrumental variables account for changing personality traits. We find that most of our social capital measures have a significant and positive impact on the probabilities for investing in various types of adult learning. The size of the effect varies across the different measures between increasing the probability of participating in adult learning by 0.04% to increasing the probability by 17%. We find evidence that acquaintances are more likely to increase participation in adult learning than friends.
Keywords: 330; social capital; lifelong learning; informal learning; trust; reciprocity; sociability